Especificação de um framework para rastreabilidade da cadeia produtiva de grãos - Vaz, Monica Cristine Scherer (2014)
Traceability allows to identify the product’s origin and route, at any time of its production chain, main requirement in normalization processes, certifications and in quality management systems. About food products, where contamination acciddent’s impact involves health damage, traceability allows that the affected lots may be detected and quickly removed from the market with safety, minimizing losses. Besides legal requirements about traceability, the final consumer is looking for having access to informations about food which are being eaten, motivating tecnological solution’s development in this area. The goal of this dissertation is to present the specification of RastroGrão Framework, to traceability of productive grains process. This Framework is based in regulations and rules of quality applied to traceability and in systems of grains traceability, allowing records relative to production’s processes. These records can be changing according to the necessity of each participant agent of production chain. Data to be traced are recorded by the user, not being necessary system maintenance everytime it appears a new requirement to be traced. To the development of Framework was used Java Language to WEB Environment and PostgreSQL Database. The main contribution of this dissertation are related to the benefits offered by the Framework are: i) visibility of informations, which can be accessed through internet, by all the chain agents; ii) integration of all links of the productive chain; and iii) information’s availability to the final consumer through QR-Code, that can be accessed in the internet or printed on the packaging.